Safety and Efficacy of Ritlecitinib and Brepocitinib in Alopecia Areata: Results from the Crossover Open-Label Extension of the ALLEGRO Phase 2a Trial - Brett King; Emma Guttman-Yassky; Elena Peeva; Anindita Banerjee; Linda Zhu; Hua Zhu; Lori Ann Cox; Michael S. Vincent; Rodney Sinclair (Elsevier, 2022)
The 24-week, double-blind period of the ALLEGRO phase 2a trial (NCT02974868) evaluated the safety and efficacy of ritlecitinib (Jak3/tyrosine kinase expressed in the hepatocellular carcinoma inhibitor) and brepocitinib (tyrosine kinase 2/Jak1 inhibitor) in patients with alopecia areata; patients could subsequently continue treatment in a 24-week single-blind extension, followed by a crossover open-label extension, described in this article. Patients who did not achieve ≥30% improvement from baseline in Severity of Alopecia Tool score at the end of the single-blind extension entered a 24-week crossover open-label extension: the ritlecitinib group switched to brepocitinib, and the brepocitinib group switched to ritlecitinib. Eighteen patients switched to brepocitinib, and five switched to ritlecitinib. Six treatment-emergent adverse events were reported by five patients; no new safety risks were observed after crossover. An exploratory efficacy evaluation showed that none of the five patients receiving ritlecitinib in the crossover open-label extension achieved ≥30% improvement from baseline in Severity of Alopecia Tool score or improvement in eyebrow/eyelash assessments. Four of 16 patients receiving brepocitinib achieved ≥30% improvement from baseline in Severity of Alopecia Tool score or better; 4 of 15 and 5 of 12 showed improvement in eyebrow and eyelash assessments, respectively. Although the small number of patients precludes firm conclusions regarding efficacy, the data suggest that some patients with alopecia areata and inadequate response to ritlecitinib after ≥24 weeks show benefit after switching to brepocitinib.